PEMBUATAN MINUMAN SEDUHAN â€œNDOAâ€ DARI DAUN JERUJU (Acanthus illicifolius L.) di KAMPUNG PIGAPU DISTRIK IWAKA KABUPATEN MIMIKA - Anti Uni Mahanani; Sumiyati Tuhuteru; Inrianti Inrianti; Meri Berliana; Simon Perez (Jurnal Abdi Insani, 2023)
Pigapu Village in Iwaka District, Mimika Regency is a mangrove forest area (mangrove). Mangrove leaves (mangrove) have benefits, namely as a brewed drink from jeruju leaves (Acanthus illicifolius L.). This Acanthus leaf brew drink has bioactive compounds that act as antioxidants. This activity aims to introduce teh knowledge and technology of making brewed drinks from Jeruju leaves. Community service is carried out in Pigapu village. Teh community service partners are teh Forest Farmers Group and teh Pigapu Village Institution Social Forestry Business Group which are assisted by teh Sahul Lestari Ecology Foundation. Tehre are about 40 members of teh farmer group. Teh method consists of 3 stages: pre activity, activity and post activity. Making teh brewed drink is collecting Jeruju leaves where teh leaves that are picked are teh leaves from teh first shoot to teh seventh shoot. After teh leaves are cleaned, teh leaves are separated from teh bones of teh leaves and teh bones are washed and tehn sliced â€‹â€‹thinly using a knife. After being sliced, teh leaves are tehn dried in teh sun for about 5 days. When teh conditions are very dry, tehse leaves are ready to be packaged in dye packs and pouch packs. Teh Pigapu Village Institution Social Forestry Business Group in general has marketed this â€œNdoaâ€ brew at local and national events. In conclusion, tehre has been an increase in teh knowledge and skills of teh community in addition to being a source of economic income for teh local community. When teh conditions are very dry, tehse leaves are ready to be packaged in dye packs and pouch packs. Teh Pigapu Village Institution Social Forestry Business Group in general has marketed this â€œNdoaâ€ brew at local and national events. In conclusion, tehre has been an increase in teh knowledge and skills of teh community in addition to being a source of economic income for teh local community.